Ethical Dimensions in Digital Marketing: A Systematic Literature Review - Ahmed Abdulkareem Alanisi; Bahareh Abedin; Morteza Movaghar; Abolhasan Hosseini; Erne Suzila Kassim (International Journal of Management, Accounting and Economics, 2025)
This study conducts a systematic review of the literature concerning the ethical requirements of digital marketing, focusing on the evolving landscape over the past two decades. As digital marketing becomes increasingly integral to business strategies, understanding its ethical implications is crucial for maintaining consumer trust and compliance with legal standards. This research aims to examine the ethical principles that guide digital marketing and to analyze, combine, and classify key findings from previous studies. Following a rigorous systematic literature review (SLR) method based on PRISMA and the framework of Xiao and Watson (2017), this review analyzes 55 peer-reviewed articles published between 2000 and 2024. The study identifies nine key ethical dimensions, including ethics related to product and service, promotion, salesperson conduct, religion, place, ethical norms, internet space, price, and decision-making. Through thematic analysis, it develops an integrative conceptual framework that synthesizes deontological ethics, stakeholder theory, and culturally grounded paradigms such as Islamic business ethics. The findings emphasize the importance of embedding ethical values in digital strategies to ensure legal and moral alignment. This review offers both theoretical and practical contributions by proposing a multi-dimensional model of digital marketing ethics tailored to challenges such as AI-driven personalization, data privacy, and misinformation. It provides actionable insights for scholars and practitioners seeking to navigate ethical complexities in the digital marketing ecosystem.